Comparative Analysis on Roof Covering Materials Sustainability as Constructed by Bamboo and Corrugated Galvanized Iron Sheet in Rural Areas Around Wolkite, Ethiopia - Abera , Hailu; Elmer C. Agon; Mamaru Dessalegn (International Journal of Sustainable Construction Engineering and Technology, 2022)
One of the most important components of any building is the roof, which protects the interior of the building from environmental influences. It is sustainable to switch roofing materials from expensive roofing materials to inexpensive and environmentally friendly materials. Today’s roofing materials have negative effects on the environment due to the manufacturing process. Therefore, this research has mainly focused on the development of sustainable roofing materials through life cycle cost analysis. Approximately ten bamboo samples from homeowners in the Wolkite area and one Adama corrugated galvanized sheet were taken to analyze the life cycle costs. Data on the ecological and socio-economic aspects of the selected roofing materials were collected with the help of interviews and questionnaires. The cost of galvanized corrugated iron sheet of 1.8m2 was 38.19 while the cost of bamboo was 3.91; the researchers concluded that treated bamboo roofs have lower life cycle costs per 1.8 square meters (approximately 89.76% less than corrugated galvanized iron), more environmentally friendly. And also using bamboo as roofing material, create a good job opportunity for the society by cultivating and preparing bamboo to the construction input.